2014
DOI: 10.1073/pnas.1405879111
|View full text |Cite
|
Sign up to set email alerts
|

Specific collagen XVIII isoforms promote adipose tissue accrual via mechanisms determining adipocyte number and affect fat deposition

Abstract: Collagen XVIII is an evolutionary conserved ubiquitously expressed basement membrane proteoglycan produced in three isoforms via two promoters (P). Here, we assess the function of the N-terminal, domain of unknown function/frizzled-like sequences unique to medium/long collagen XVIII by creating P-specific null mice. P2-null mice, which only produce short collagen XVIII, developed reduced bulk-adiposity, hepatic steatosis, and hypertriglyceridemia. These abnormalities did not develop in P1-null mice, which prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 55 publications
4
88
0
Order By: Relevance
“…The N‐terminal domain of the long isoform inhibits the wnt‐beta catenin pathway, via a Frizzle‐like sequence . In addition, lack of collagen 18 increases the number of adipocyte progenitors in the liver . Thus, collagen 18 could exert relevant functions in bone biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N‐terminal domain of the long isoform inhibits the wnt‐beta catenin pathway, via a Frizzle‐like sequence . In addition, lack of collagen 18 increases the number of adipocyte progenitors in the liver . Thus, collagen 18 could exert relevant functions in bone biology.…”
Section: Discussionmentioning
confidence: 99%
“…(42) In addition, lack of collagen 18 increases the number of adipocyte progenitors in the liver. (43) Thus, collagen 18 could exert relevant functions in bone biology. However, 2-and 4-weekold unchallenged Col 18 alpha1 -/mice have no obvious bone phenotype.…”
Section: Ipth Upregulates Pedf and Collagen 18 Expressionmentioning
confidence: 99%
“…It is mediated by fibrinolytic factors, such as plasminogen and plasmin, matrix metalloproteases (MMP), and antifibrinolytic systems like the tissue inhibitors of MMP (TIMPs), among others . Studies in individuals with obesity have reported the relation between body mass index, ECM components, and metabolic disorders in adipose tissue . Experiments in mice lacking collagen VI, the most abundant type in adipose tissue, in an ob/ob background, showed larger adipocytes and improved metabolic parameters, suggesting that collagen VI may constraint adipocytes, provoking metabolic alterations .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, aortic explants isolated from Col18a1 −/− mice show increased angiogenesis compared to wild-type mice [43]. Recently, collagen XVIII has been implicated in the pathogenesis of renal ischemia/reperfusion as a mediator of leukocytic influx [44], and in hyperlipidemia associated with fatty liver and visceral obesity, suggesting that it might play a role in the adipose tissue formation [45]. …”
Section: Collagen XVIIImentioning
confidence: 99%